2021
DOI: 10.3889/oamjms.2021.7399
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy and Acceptance among Medical Students: An Online Cross-sectional Study in Iraq

Abstract: BACKGROUND: Vaccine hesitancy and reluctant had an important obstacle in achieving protection and population immunity against coronavirus disease 19 (COVID-19). It is essential to achieve high COVID-19 vaccination acceptance rates among medical students and health care workers to provide recommendations and counseling vaccine hesitant population. AIM: This study aims to identify level of COVID-19 hesitancy, attitude, knowledge, and factors that affect vaccination decision. MATERIALS AND METHODS: A cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…This indicates a much lower hesitancy rate among medical students than in Sudan, United States, and Iraq where hesitancy rates were 44.2%, 47%, and 65.22%, respectively. 4 , 8 , 11 Although compared to our findings, a lower vaccine hesitancy rate was demonstrated among medical students in India and Japan, 16.57% and 10.9%, respectively. 8 , 12…”
Section: Discussioncontrasting
confidence: 84%
“…This indicates a much lower hesitancy rate among medical students than in Sudan, United States, and Iraq where hesitancy rates were 44.2%, 47%, and 65.22%, respectively. 4 , 8 , 11 Although compared to our findings, a lower vaccine hesitancy rate was demonstrated among medical students in India and Japan, 16.57% and 10.9%, respectively. 8 , 12…”
Section: Discussioncontrasting
confidence: 84%
“…The total estimated COVID-19 vaccination hesitancy rates among HCSs was 25.8% (95%CI: 18.5–33.8% I 2 = 99%) ( Figure 3 ). Mahdi [ 50 ] reported the highest hesitancy rates in Iraq (66.2%, 95%CI: 62.8–69.4%), and the lowest rate of hesitancy was found in Poland (3.9%, 95% CI: 2.6–5.7%) by Szmyd et al [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…This feeling was not exclusive to members of the public only, but it was also demonstrated among health professionals and university students. For example, Mahdi [19], has reported that vaccine hesitancy among Iraqi medical students was up to 65.21% [19]. Similarly, other studies conducted among professional groups and university students showed a high rate of hesitancy towards accepting the COVID-19 vaccine [20][21][22].…”
Section: Introductionmentioning
confidence: 99%